Bakhar: A Tradition of Marathi Historiography - Magar, Rahul V. (Vidyapith (વિદ્યાપીઠ), 2020)
Historiography is the study of history, particularly the study of history based on the critical evaluation of sources, the selection of specific facts from authentic materials in those sources, and the synthesis of those details into a narrative that can withstand critical inquiry. The cultural, political and ideological views of the writers or historians could possibly be reflected in historical texts and books. Historiography can be used to examine how history emerged as a distinct discipline over the years. There are many traditions and perspectives of history writing and graphy, therefore, this paper explores the 'Bakhar' as a Marathi historiography tradition. Bakhar is a type of Marathi history writing that emerged during the mediaeval period. It is typically written in Marathi's Modi script in the form of prose. Bakhar is regarded as an important source of Maratha history, but scholars often disagreed with its authenticity and dependability.